KATA NAHNU SEBAGAI KATA GANTI ALLAH DALAM AL-QUR’AN (Studi Komparatif Kitab Tafsir Al-Kasysyaf dan Tafsir Al-Qur’an Al-‘Azhim) - HAFIZ HAFIZ; Moh. Isa Anshary; R.A. Erika Septiana (Al-Misykah: Jurnal Studi Al-qur'an dan Tafsir, 2021)
This research is categorized as literature research. The primary sources of this research are the Tafsir Al-Qur'an Al-'Azhim and the Tafsir Al-Kasysyaf. Meanwhile, the secondary sources are all matters that related to this discussion. The composition of the verses of the Al-Qur'an is concise yet full of meanings that adding to the i'jaz uslub contained in it. One of the example is the pronoun or dhamir nahnu. The use of dhamir nahnu in the Qur'an is not only used as a plural for first-person pronoun, but is also used as a pronoun for Allah. Nahnu as a pronoun for Allah does not mean that Allah is numbered, because in Islamic understanding it explains that Allah is the oneness. The use of lafazh nahnu as a pronoun for Allah has its own purposes, such as a form of adoration or respect and as a show of His power. Based on this phenomenon, the researcher studied the lafazh nahnu as a pronoun for Allah in the Al-Qur'an by composing the Al-Qur'an Al-'Azhim tafsir book by Ibnu Katsir and the Al-Kasysyaf tafsir book by Az-Zamakhsyari. To study these verses, the writer uses jumlah ismiyyah, fi’liyyah and dhamir principles as analytical tools. The researcher focuses on verses that have lafazh nahnu as a pronoun for Allah in the Al-Qur'an. After analyzing the interpretation of these verses, it was found that the interpretation of verses with dhamir nahnu as a pronoun for Allah aims as a form of glorification or reinforcement of His power.